Development of educational game-based learning media to improve mastery of ecosystem material in high school students - Syifa Rahmah; Listika Yusi Risnani (Practice of The Science of Teaching Journal: Jurnal Praktisi Pendidikan, 2023)
Advances in science and information technology currently have a major influence in various fields of life, one of which is the field of education. In the field of education, the implementation of learning in schools should utilize information and communication technology to support the efficiency and effectiveness of learning. Information and communication technologies that can support the learning process in the classroom include educational game learning media. This study aims to develop educational games on ecosystem material for class X SMA. The development model used in this study is the ADDIE model, namely: 1) analysis, 2) Design, 3) Development, 4) Implementation and 5) Evaluation. This study used an instrument in the form of a questionnaire and pretest posttest questions. The questionnaire assessment data were analyzed using quantitative descriptive, while the pretest and posttest data were validated by N-Gain. The results of this study are: game assessment by media experts with an average score of 3.73 (very good), game assessment by material experts with an average score of 3.21 (good), teacher assessment with an average of 3.16 (good), and assessment by students with an average score of 3.09 (good). The results of the students' pretest and posttest based on the N-Gain calculation, namely 0.44 were included in the medium category. Based on the results of the study, it can be concluded that educational games on ecosystem materials for class X SMA are suitable for use as learning media in the classroom based on the results of the feasibility test of media experts, material experts, teachers and students. Abstrak. Kemajuan ilmu pengetahuan dan teknologi informasi saat ini berpengaruh besar dalam berbagai bidang kehidupan, salah satunya adalah  bidang pendidikan. Pada bidang pendidikan pelaksanaan pembelajaran di sekolah hendaknya memanfaatkan teknologi informasi dan komunikasi untuk menunjang efisiensi dan efektivitas pembelajaran. Teknologi informasi dan komunikasi yang dapat menunjang proses pembelajaran di kelas antara lain yaitu dengan media pembelajaran  game edukasi. Penelitian ini bertujuan untuk mengembangkan game edukasi pada materi ekosistem kelas X SMA. Model pengembangan yang digunakan dalam penelitian ini adalah model ADDIE, yaitu: 1) analysis, 2) Design, 3) Development, 4) Implementation dan 5) Evaluation. Penelitian ini menggunakan instrument berupa angket dan soal pretest postest data penilaian angket dianalisis dengan menggunakan deskriptif kuantitatif sedangkan data pretest dan postest dengan validasi N-Gain. Hasil penelitian ini berupa: penilaian game oleh ahli media dengan rata-rata skor 3,73 (baik sekali), penilaian game oleh ahli materi dengan rata-rata skor 3,21 (baik), penilaian oleh guru dengan rata-rata 3,16 (baik), dan penilaian oleh siswa dengan rata-rata skor 3,09 (baik). Hasil pretest dan posttest siswa berdasarkan perhitungan N-Gain yaitu 0,44 termasuk dalam kategori sedang. Berdasarkan hasil penelitian dapat disimpulkan bahwa game edukasi pada materi ekosistem kelas X SMA layak digunakan sebagai media pembelajaran di kelas diluhat dari hasil uji kelayakan ahli media, ahli materi, guru dan siswa. Kata kunci: ADDIE; game edukasi; ekosistem